FAKTOR DETERMINAN PEMILIHAN PROFESI AKUNTAN PUBLIK DALAM PERSEPSI MAHASISWA AKUNTANSI SYARIAH INSTITUT AGAMA ISLAM SYARIFUDDIN (IAIS) LUMAJANG - Mudhofar, Muhammad; Wibisono, Yusuf (Universitas Muhammadiyah Jember, 2024)
Abstract: Public accounting is a strategic profession in the business and monetary world with a special competency background. Students in the sharia accounting study program are at a linear level of education with the public accounting profession. Students' choice of a career as a public accountant is influenced by several perceptions. This research aims to examine and analyze perceptions of market considerations, financial rewards, social values, and professional recognition of the public accounting profession. The research sample was IAIS Lumajang sharia accounting students using the Slovin theory sampling technique. Data collection was obtained from distributing questionnaires via online Google Form. The data was processed by statistical tabulation using multiple linear regression analysis techniques with the statistical product and service solutions (SPSS) program. The research results show that the variable perception of market considerations influences the choice of the public accounting profession. The variables of financial rewards, social values, and professional recognition have no effect on the public accounting profession. The implication of the suggestion is that the results of this research cannot be generalized to the population and subsequent research can use data from a wider range of research objects.Keywords: Perception, Students, Public Accountants.